Pemenuhan Kebutuhan Dasar Peserta Didik Sekolah Menengah Atas (SMA) dalam Perspektif Hierarki Kebutuhan Maslow - An Falah, Allaam; Putra, Fuaddillah; Rahma Mulyani, Rila (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe the profile of meeting the basic needs of class X students at SMA Negeri 13 Padang based on Abraham Maslow's hierarchy of needs theory, which includes physiological, sense of security, sense of belonging and affection, appreciation, and self-actualization. Fulfilling these needs is important in supporting students' learning readiness and psychological well-being. The research method used a descriptive quantitative approach with a sample of 80 students of class X selected through purposive sampling. The instrument is in the form of a closed questionnaire that has been tested for validity and reliability. The data was analyzed with descriptive statistics to describe the conditions of meeting needs without making generalizations. The results of the study show that the fulfillment of the basic needs of students in general is in the category of being quite met. In physiological aspects, sense of security, love and affection, and appreciation, the majority of students are in the high category. These findings affirm the importance of the role of schools, teachers, and parents in supporting the basic needs of students so that they can support the success of the educational process both academically and psychologically.